Peran Kepemilikan Manajerial dalam Hubungan Antara Tingkat Utang, Siklus Operasi, dan Ukuran Perusahaan Terhadap Persistensi Laba - Pratiwi, Surya Asih; Suwarno, Agus Endro (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the effect of debt level, operating cycle, and firm size on earnings persistence with managerial ownership as a moderating variable in consumer goods companies listed on the Indonesia Stock Exchange in 2020 – 2022. The data used in this study are data secondary with the sampling technique using purposive sampling based on certain criteria so that 53 companies were selected as research samples. Data analysis used multiple linear regression analysis using SPSS 25. The result showed that debt level and operating cycle had an effect on earnings persistence, while firm size had no effect on earnings persistence. Debt level, operating cycle, and firm size moderated by managerial ownership have no effect on earnings persistence.